Zora Neale Hurston : collected plays - Hurston, Zora Neale; Cole, Jean Lee.; Mitchell, Charles, 1967- (New Brunswick, N.J. : Rutgers University Press, 2008)
Though she died penniless and forgotten, Zora Neale Hurston is now recognized as a major figure in African American literature. Best known for her 1937 novel Their Eyes Were Watching God, she also published numerous short stories and essays, three other novels, and two books on black folklore. Even avid readers of Hurston's prose, however, may be surprised to know that she was also a serious and ambitious playwright throughout her career. Although several of her plays were produced during her lifetime-and some to public acclaim-they have languished in obscurity for years. Even now, most critics and historians gloss over these texts, treating them as supplementary material for understanding her novels. Yet, Hurston's dramatic works stand on their own merits and independently of her fiction. Now, eleven of these forgotten dramatic writings are being published together for the first time in this carefully edited and annotated volume. Filled with lively characters, vibrant images of rural and city life, biblical and folk tales, voodoo, and, most importantly, the blues, readers will discover a "real Negro theater" that embraces all the richness of black life
Meet the mamma (1925) -- Color struck (1926) -- The first one (1927) -- Cold keener (1930) -- De turkey and de law (1930; with Langston Hughes) -- The sermon in the valley (1931; with Rowena Woodham Jelliffe) -- Four plays from Fast and furious (1931). Woofing ; Lawing and jawing ; Forty yards ; Poker! -- The fiery chariot (1932) -- Spunk (1935) -- Polk county (1944; with Dorothy Waring).
Includes bibliographical references (pages 387-389).
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Hurston, Zora Neale -- 1891-1960; Hurston, Zora Neale; African Americans -- Drama; American drama; Théâtre américain.; DRAMA -- American; DRAMA -- American -- General; African Americans; Drama; Drama; Théâtre.